1967
DOI: 10.1139/m67-063
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Spheroplasts of Mycobacterium Tuberculosis by Lysozyme in Combination With Certain Enzymes of Rabbit Peritoneal Monocytes

Abstract: Spheroplasts of Mycobacterium tuberculosis were formed by culture of the organism in a nutritionally complete medium to which lysozyme and an extract obtained from rabbit peritoneal monocytes were added. The potentiating effect of the factor, or factors, present in the monocyte extract was lost upon prolonged storage at −20 °C or heat at 90 °C for 5 minutes, but was unaffected by dialysis. It was inactive in the presence of fluoride or oxalate. Enzymatic analysis of the monocyte extract showed the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The accumulation ofenough host macromolecules about the surface of Phe I should render it somewhat indistinguishable from the host's self Most Phe I appear to have an intact cell wall. This is interesting in light of the fact that Willet and Thacore found that either acid phosphatase or phospholipase C could render H37Ra susceptible to lysozyme, with subsequent protoplast formation (1263) and, with high enough numbers of bacteria, even L-form development (1262). The addition of lysozyme to cell cultures of J-111 human monocytes has made possible the formation of protoplasts in these host cells (1147).…”
Section: Arabinogalactan and Arabinogalactan-mycolatementioning
confidence: 99%
“…The accumulation ofenough host macromolecules about the surface of Phe I should render it somewhat indistinguishable from the host's self Most Phe I appear to have an intact cell wall. This is interesting in light of the fact that Willet and Thacore found that either acid phosphatase or phospholipase C could render H37Ra susceptible to lysozyme, with subsequent protoplast formation (1263) and, with high enough numbers of bacteria, even L-form development (1262). The addition of lysozyme to cell cultures of J-111 human monocytes has made possible the formation of protoplasts in these host cells (1147).…”
Section: Arabinogalactan and Arabinogalactan-mycolatementioning
confidence: 99%
“…The methods for removing the cell wall by lysozyme have been used with success on a variety of bacteria. However, protoplasts of mycobacterial cells were not readily prepared by lysozyme alone, since the complex nature of mycobacterial cell wall makes these organisms relatively resistant to the action of lysozyme (8,10). Some strains of rapidly growing mycobacteria and of strain BCG, when grown in the presence of lysozyme and glycine, become osmotically sensitive forms believed to be spheroplasts (1,(4)(5)(6).…”
mentioning
confidence: 99%
“…DISCUSSION Degradation with enzymes offers a way other than classical chemical extraction for the study of mycobacterial cell wall antigens. Although mycobacteria are relatively resistant to degradation by lysozyme, several investigators have reported alteration of isolated mycobacterial cell walls by this enzyme (8,14,16,17). In the work reported here, we wished clearly to distinguish between wall and nonwall antigens.…”
Section: Resultsmentioning
confidence: 94%